Total Synthesis of (+)-Clavulatriene A - Ito, Fumihiro; Ohbatake, Yuki; Aoyama, Satoshi; Ikeda, Tatsuya; Arima, Shiho; Yamada, Yuuki; Ikeda, Haruo; Nagamitsu, Tohru (Synthesis, 2015)
The protecting-group-free total synthesis of (+)-clavulatriene A has been achieved. Key features of the synthetic strategy include the development of a novel strategy for the practical synthesis of α-cyperone, and a one-pot palladium-catalyzed reductive desulfonylation and deacetoxylation reaction. Furthermore, the total synthesis described in this study allowed for the determination of the absolute configuration of (+)-clavulatriene A.
Keywords: protecting-group-free; total synthesis; clavulatriene A; absolute configuration